Regulation of the Acute Sickness Response by the P2RX7 Receptor. (20th January 2021) - Li, Hui; Cvejic, Erin; Gu, Ben; Vollmer-Conna, Ute; Hickie, Ian; Wakefield, Denis; Davenport, Tracey; Wiley, James; Lloyd, Andrew R
Abstract: Background: The acute sickness response to infection is a stereotyped set of illness manifestations initiated by proinflammatory signals in the periphery but mediated centrally. P2RX7 is a highly polymorphic gene encoding an ATP-gated cationic pore, widely expressed on immune cells and the brain, and regulating the NLRP3 inflammasome, as well as diverse neural functions. Methods: Associations between P2RX7 genotype, pore activity, and illness manifestations were examined in a cohort with acute viral and bacterial infections (n = 484). Genotyping of 12 P2RX7 function-modifying single-nucleotide polymorphisms (SNPs) was used to identify haplotypes and diplotypes. Leucocyte pore activity was measured by uptake of the fluorescent dye, YO-PRO-1, and by ATP-induced interleukin-1β (IL-1β) release. Associations were sought with scores describing the symptom domains, or endophenotypes, derived from principal components analysis. Results: Among the 12 SNPs, a 4-SNP haplotype block with 5 variants was found in 99.5% of the subjects. These haplotypes and diplotypes were closely associated with variations in pore activity and IL-1β production. Homozygous diplotypes were associated with overall illness severity as well as fatigue, pain, and mood disturbances. Conclusions: P2RX7 signaling plays a significant role in the acute sickness response to infection, likely acting in both the immune system and the brain. Abstract : Homozygous variations in the highly polymorphic, purinergic receptor gene, P2X7, are associated with both pore activity and severity of the acute sickness response to infection.